Embebição e osmocondicionamento como indutores de germinação de sementes florestais potenciais para a semeadura direta - Oliveira, Andreliza Roberta Terciotti de (Universidade Federal de São Carlos, 2023)
Some forest species used in direct seeding present low emergence in the field, such as Croton urucurana Baill., Gallesia integrifolia (Spreng.) Harms, Handroanthus heptaphyllus (Vell) Mattos, Jacaranda cuspidifolia Mart and Schinus terebinthifolia Raddi. In order to know the germination pattern, sought through the Systematic Literature Review information that would complete gaps in order to elaborate protocols of soaking and osmoconditioning for the target species. For the soaking test, four replicates of 25 seeds were used, it was conditioned in germitest paper rolls damred with distilled water, in the proportion of two and a half times its mass and were kept in BOD at 25° C and photoperiod of 12 hours. In the first 12 hours, they were weighed on a precision scale (0.0001g) at one-hour intervals and after every 24 hours until the protrusion of the radicle. From the weight obtained, the embebition curve was constructed. The species presented different embebition velocity, being 4 days (96h) for S. terebinthifolia and G. integrifolia, 5 days (120h) for H. heptaphyllus and 7 days (168h) for C. urucurana and J. cuspidifolia, the period in which germination began. Seed osmoconditioning was performed with Polyethylene glycol 6000 at osmotic concentrations (0.0, -0.6, -0.9, -1.2, -1.5 MPa), in the periods of 12, 24, 48, 72, 96 and 120 hours. The osmoconditioning of the seeds was carried out with Polyethylene glycol 6000 at osmotic concentrations (0.0, -0.6, -0.9, -1.2, -1.5 MPa), soaked in periods of 12, 24, 48, 72, 96 and 120 hours. The embebition in water (T0) in the period of 24h, reached germination of 72% for J. cuspidifolia, while for G. integrifolia and S. terebinthifolia in this same period of embebition, the highest percentages of germination were obtained in the treatment -0.6 and -0.9 MPa, being 59% and 78% respectively, it is inferable that the conditioning through these osmotic potentials in 24-hour instilling are promising because they favored increased germination.
Soaking and osmoconditioning as inductors of germination of potential forest seeds for direct seeding
Keywords: polietilenoglicol; padrão germinativo; condicionamento; polyethylene glycol; germination pattern; conditioning; CIENCIAS BIOLOGICAS; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL::CONSERVACAO DA NATUREZA::RECUPERACAO DE AREAS DEGRADADAS